2020
DOI: 10.21608/ejchem.2020.38753.2798
|View full text |Cite
|
Sign up to set email alerts
|

Eco-friendly secondary metabolites from Conyza dioscoridis against Spodoptera littoralis

Abstract: 2 ry metabolites of bioactive chloroform/ methanol extract of Conyza dioscoridis using chromatographic techniques and spectroscopic analysis led to identify five major compounds; β-amyrin-3-acetate, β-lupeol-3-acetate, β-amyrenone, dotriacontane and 5,4ʹ-dihydroxy-6,7-dimethoxyflavone. The percentage of cumulative mortalities during pupal and adult stages reached to 76.6% and 83.3%, respectively after feeding 4 th larval instar of Spodoptera littoralis on C. dioscoridis crude extract with insecticidal activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Among five tested plants against M. domestica, treatment of 2 nd instar larvae with a 25% concentration of Penganum harmala led to a reduction in the AchE activity (Zahoor et al, 2020). After treatment of the 4 th larval instar of S. littoralis with chloroform/methanol extract of Conyza dioscoridis aerial parts, the acetylcholinesterase activity was remarkably reduced in the larval body homogenate (Matloub et al, 2021). Results of the present study were in agreement with those reported results since the treatment of the newly moulted penultimate instar nymphs of S. gregaria with margosan-O ® resulted in a considerable inhibition of AchE activity in fat bodies of only the late-aged nymphs.…”
Section: Discussionsupporting
confidence: 92%
“…Among five tested plants against M. domestica, treatment of 2 nd instar larvae with a 25% concentration of Penganum harmala led to a reduction in the AchE activity (Zahoor et al, 2020). After treatment of the 4 th larval instar of S. littoralis with chloroform/methanol extract of Conyza dioscoridis aerial parts, the acetylcholinesterase activity was remarkably reduced in the larval body homogenate (Matloub et al, 2021). Results of the present study were in agreement with those reported results since the treatment of the newly moulted penultimate instar nymphs of S. gregaria with margosan-O ® resulted in a considerable inhibition of AchE activity in fat bodies of only the late-aged nymphs.…”
Section: Discussionsupporting
confidence: 92%
“…In cases with the use of higher concentrations of extracts (2, 4), a slight increase in vivacity was recorded (ATEN 1.0 -1.25%) or a serious decrease (AANN 1.0 -8.25%). In variants (1,3,5), where green grass was treated in solutions of agents with a lower concentration, an increase in the yield of caterpillars (revitalization) was observed by 4.50-8.75 absolute percent. In terms of production of egg, this is a fairly high percentage, indicating a significant increase in the quality of egg.…”
Section: Resultsmentioning
confidence: 98%
“…Such studies [3,4] describe the growth-regulating activity of a number of isoprenoids related to sesquiterpenoids with different types of carbon skeleton. The research results showed that the sesquiterpenoids α -santonine (1), zerumbone (2) and C16-guayanolide (3) (Figure 1), isolated from plants, increase the yield of rice after one-day soaking of seeds in their solutions at a dilution of 1: 10,000 compared to the control by 14.17% (α-santonine, zerumbone) and 7.5% (C16-guayanolide).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As one of the most important global economic problems, the protection of crops from pests is urgently needed. Many different countries search for natural alternatives to chemical dangerous pesticides using safe compound with minimal costs and ecological side effects (Matloub et al 2021). This insect is attacking more than 112 host plants mainly on vegetable, field, ornamental crops and many other economic plants.…”
Section: Introductionmentioning
confidence: 99%